1985
DOI: 10.1530/jrf.0.0740399
|View full text |Cite
|
Sign up to set email alerts
|

Follicular growth and atresia in the ovaries of hens (Gallus domesticus) with diminished egg production rates

Abstract: Summary. Diets containing 3\m=.\5,1\ m=.\0and 0\m=.\1% calcium were fed from the age of 42 weeks to individually caged laying hens. Ovaries were examined at 46\p=n-\49and 70 weeks of age for changes in the follicular population corresponding to the lowered egg production rates of birds given calcium-deficient diets (1\m=.\0% and 0\m=.\1%) and older birds given a normal diet (3\m=.\5%).Growth rates of follicles from 3\ m=. \ 5 mm diameter to ovulation were not changed by the level of dietary calcium in 46\p=n-\… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 16 publications
0
21
1
1
Order By: Relevance
“…In laying chickens, a decrease in follicular maturation rate and egg production rate late in an egg production period may be caused by a higher incidence of follicular atresia [32][33][34]. However, the present results showed that higher incidences of follicular atresia were not detected late in the reproductive period, suggesting that this phenomenon does not contribute to the decrease in egg production late in the egg production period in the Egg line of turkey hens.…”
Section: Discussioncontrasting
confidence: 63%
“…In laying chickens, a decrease in follicular maturation rate and egg production rate late in an egg production period may be caused by a higher incidence of follicular atresia [32][33][34]. However, the present results showed that higher incidences of follicular atresia were not detected late in the reproductive period, suggesting that this phenomenon does not contribute to the decrease in egg production late in the egg production period in the Egg line of turkey hens.…”
Section: Discussioncontrasting
confidence: 63%
“…In eggtype chickens, the number of large follicles in an ovary is related to the pattern of laying and birds laying in long sequences tend to have more than those laying in short sequences (Gilbert, 1971). Waddington et al (1985) also noted that the decrease in egg production in chickens was accompanied by a corresponding reduction in average sequence length.…”
Section: Discussionmentioning
confidence: 90%
“…The effects of ageing on this loss is not clear. Reductions in egg laying towards the end of a laying year have been associated with the incidence of follicular atresia (Williams and Sharp, 1978a;Waddington et al, 1985). A further decrease in egg output could be due to a condition known as erratic oviposition and defective egg syndrome (EODES) (van Middlekoop, 1972).…”
Section: Introductionmentioning
confidence: 99%